The problem of non-discrimination in labor relations - Вишновецька, Світлана Василівна; Пінчук, Ольга Борисівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The problem of discrimination on the grounds of gender and age in the field of labor relations are investigated in the article. International and Ukrainian legal regulation of non-discrimination as a guarantee of the right to work was analyzed; solutions to the problem are proposed in the article. The different points of view on the concept of discrimination in labor relations were studied by the authors. It was founded that discrimination by age and gender are the most extended forms of discrimination in the workplace today. This problem still exists in practice despite the fact that the principle of non-discrimination is normatively enshrined at both international and national levels. However employers do not follow the principle of non-discrimination in labor relations regardless of legislative ban. In spite of professional qualifications requirements for age and appearance are the obstacle for many women. Workers aged 45-60 years often have problems with employment because of stereotypes regarding older people among employers. The data on marital status, family planning and other personal information often become a ground for the decision of a possibility to get a job. Moreover women become victims discrimination in hiring, wage inequality, unstable working conditions and illegal dismissals during maternity leave. Two types of discrimination in employment are singled on the base of legislation - direct and indirect. The question of the judicial settlement of this category of labor disputes was resolved by Plenum of the Supreme Court of Ukraine. In particular court makes a positive decision for person whose employment rights was infringed and obliges the employer to conclude an employment contract. Authors consider necessary the adoption of legislative acts which directly prohibit concretization of the desired age or desired sex in job advertisements and establishing penalties for violations of the legal prohibitions on discrimination.